2023
DOI: 10.1371/journal.pgen.1010601
|View full text |Cite
|
Sign up to set email alerts
|

Conformational rearrangements in the sensory RcsF/OMP complex mediate signal transduction across the bacterial cell envelope

Abstract: Timely detection and repair of envelope damage are paramount for bacterial survival. The Regulator of Capsule Synthesis (Rcs) stress response can transduce the stress signals across the multilayered gram-negative cell envelope to regulate gene expression in the cytoplasm. Previous studies defined the overall pathway, which begins with the sensory lipoprotein RcsF interacting with several outer membrane proteins (OMPs). RcsF can also interact with the periplasmic domain of the negative regulator IgaA, derepress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…The most accepted model of communication between IgaA and the Rcs system is a control at the periplasmic side exerted by an IgaA-RcsF interaction [ 10 , 12 ], which is relieved upon stress, an alteration that is supposed to be translated to cytoplasmic regions of IgaA. This model, however, contrasts at some extent with our functional studies with IgaA from different Enterobacterales families and the structural in silico analyses presented here.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…The most accepted model of communication between IgaA and the Rcs system is a control at the periplasmic side exerted by an IgaA-RcsF interaction [ 10 , 12 ], which is relieved upon stress, an alteration that is supposed to be translated to cytoplasmic regions of IgaA. This model, however, contrasts at some extent with our functional studies with IgaA from different Enterobacterales families and the structural in silico analyses presented here.…”
Section: Discussioncontrasting
confidence: 91%
“…Various studies have shown that IgaA interacts directly with outer membrane lipoprotein RcsF [ 10 , 12 ] and the inner membrane protein RcsD [ 6 , 7 ]. These interactions represent the activated and resting states of the Rcs phosphorelay, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the Bam complex stability does not always correlate with function (McCabe et al, 2017), we used RcsF/OMP assembly as a direct functional readout. In the absence of BamE cells fail to assemble RcsF complex with partner OMPs (Lach et al, 2023), but we use OmpA as a convenient readout in the formaldehyde crosslinking experiments (Tata et al, 2021; Tata & Konovalova, 2019). RcsF/OmpA complex is significantly reduced in the absence of BamE, and instead, RcsF accumulated on BamA (Figure 3c).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research provided the first direct evidence of the specialized functions of Bam lipoproteins by demonstrating that BamE is uniquely required for the assembly of the OM complex between the lipoprotein RcsF and its OMP partners (Konovalova et al, 2016; Tata & Konovalova, 2019). The RcsF/OMP complexes function in the Regulator of Capsule Synthesis (Rcs) stress response, allowing RcsF to monitor the integrity of the OM (Lach et al, 2023; Tata et al, 2021). Identification of the RcsF/OMP complexes as the first substrate of the Bam complex that requires BamE activity presented an opportunity to study a molecular function of BamE.…”
Section: Introductionmentioning
confidence: 99%